Increased lipid production by heterologous expression of AtWRI1 transcription factor in Nannochloropsis salina - Kang, Nam Kyu (Biotechnol Biofuels, 2017)
BACKGROUND: Genetic engineering of microalgae is necessary to produce economically feasible strains for biofuel production. Current efforts are focused on the manipulation of individual metabolic genes, but the outcomes are not sufficiently stable and/or efficient for large-scale production of biofuels and other materials. Transcription factors (TFs) are emerging as good alternatives for engineering of microalgae, not only to increase production of biomaterials but to enhance stress tolerance. Here, we investigated an AP2 type TF Wrinkled1 in Arabidopsis (AtWRI1) known as a key regulator of lipid biosynthesis in plants, and applied it to industrial microalgae, Nannochloropsis salina. RESULTS: We expressed AtWRI1 TF heterologously in N. salina, named NsAtWRI1, in an effort to re-enact its key regulatory function of lipid accumulation. Stable integration AtWRI1 was confirmed by RESDA PCR, and its expression was confirmed by Western blotting using the FLAG tag. Characterizations of transformants revealed that the neutral and total lipid contents were greater in NsAtWRI1 transformants than in WT under both normal and stress conditions from day 8. Especially, total lipid contents were 36.5 and 44.7% higher in NsAtWRI1 2–3 than in WT under normal and osmotic stress condition, respectively. FAME contents of NsAtWRI1 2–3 were also increased compared to WT. As a result, FAME yield of NsAtWRI1 2–3 was increased to 768 mg/L/day, which was 64% higher than that of WT under the normal condition. We identified candidates of AtWRI1-regulated genes by searching for the presence of the AW-box in promoter regions, among which lipid metabolic genes were further analyzed by qRT-PCR. Overall, qRT-PCR results on day 1 indicated that AtWRI1 down-regulated TAGL and DAGK, and up-regulated PPDK, LPL, LPGAT1, and PDH, resulting in enhanced lipid production in NsAtWRI1 transformants from early growth phase. CONCLUSION: AtWRI1 TF regulated several genes involved in lipid synthesis in N. salina, resulting in enhancement of neutral lipid and FAME production. These findings suggest that heterologous expression of AtWRI1 TF can be utilized for efficient biofuel production in industrial microalgae. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-017-0919-5) contains supplementary material, which is available to authorized users.